Hubungan Beban Kerja Perawat dengan Keselamatan Pasien - Syahputri, Asri Ardiani (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
1024x768 Safety is one of important thing in any health care. Therefore, when providing nursing care to patients, nurses must be able to ensure that nursing services are given priority to patient safety. One aspect of nursing professionalism can be seen in the implementation of patient safety. If the implementation of patient safety can lead to reduce bad effects in patients. Patient safety can be affected by various factors one of them is nurse workload. This study aims to determine the relationship of workload with patient safety. This study used a descriptive research design with cross sectional correlation. This research applied descriptive research design with cross sectional approach. The research sample of 25 respondents, who selected by the way of totaly sampling technique, with Spearman Rank Test and the degree of significance ? = 0.05 (5%). The results showed that the workload of nurses in the MS room Sanglah hospital that 18 nurses (72%) that have a high workload, 6 nurses (24%) had a moderate workload, and 1 nurse (4%) had a low workload. The Medical Records (MR) showed that the lowest level of patient safety is 12 MR (48%). There are only 2 MR (8%)of patient safety at a good level, and there were 11 MR (44%) with the moderate level in patient safety. The results of the Spearman's rho statistical test seen from p-value (sig.2-tailed = 0.000) <value ? = 0.05. This means that Ho is rejected and Ha accepted. So, there is a corelation between the workload of nurses with patient safety in Medical surgical room Sanglah Hospital. The strength of corelation seen in the C (Coeffisient Correlation) of 0.674 which indicates a strong corelation between the two variables. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: workload; patient safety